Regional distribution and factors associated with early marriage in Ghana: a cross-sectional study - Bright Opoku Ahinkorah; Augustus Osborne; Regina Mamidy Yillah; Camilla Bangura; Richard Gyan Aboagye (BMC, 2024)
Abstract Background Early marriage, the formal or informal union before age 18, remains a critical challenge in several low-and middle-income countries. It has adverse health and education-related implications on child brides. This study examined the regional distribution of early marriage and its associated factors in Ghana. Methods We performed a cross-sectional analysis of data extracted from the 2022 Ghana Demographic and Health Survey. Our study comprised 10,098 ever married/cohabiting aged 15 to 49. Regional variations in the prevalence of child marriage were visualised using a spatial map. A mixed-effect multilevel binary logistic regression analysis was performed to assess the factors associated with early marriage. The results were presented as adjusted odds ratios (aOR) with a 95% confidence interval (CI). Results The prevalence of early marriage was 29.2% [27.9, 30.6] in Ghana. Women in the North East 38.2% [33.4, 43.2], Western North 36.7% [32.1, 41.5] and Ahafo regions 35.8% [32.0, 39.8] had the highest prevalence of early marriage, whilst women in the Western 22.2% [18.4, 26.5] and Greater Accra 19.7% [15.8, 24.3 regions] had the lowest prevalence of early marriage in Ghana. The odds of early marriage was lower among women aged 20-49 compared to those aged 15-19. Women with secondary [aOR = 0.40; 95% CI 0.33, 0.48] and higher education [aOR = 0.07; 95% CI 0.04, 0.12], those who belonged to the Gurma ethnic group [aOR = 0.59; 95% CI 0.41, 0.84], and women from richer [aOR = 0.64; 95% CI: 0.47, 0.87] and richest [aOR = 0.42; 95% CI 0.28, 0.64] households were less likely to be married early compared to those with no education, those belonging to the Akan ethnic group, and those from the poorest wealth quintile households, respectively. The odds of early marriage was higher among women whose family size was five or more [aOR = 1.50; 95% CI 1.31, 1.72] and women living in the Central [aOR = 1.72; 95% CI 1.16, 2.54], Volta [aOR = 1.97; 95% CI 1.17, 3.30], Eastern [aOR = 1.53; 95% CI 1.01, 2.29], Ashanti [aOR = 1.98; 95% CI 1.33, 2.97], Western North [aOR = 1.77; 95% CI 1.18, 2.65], and Ahafo regions [aOR = 1.74; 95% CI 1.18, 2.56]. Conclusion About one in three marriages were early in Ghana, with variations across the regions. Age, wealth index, ethnicity, level of education, family size, and region were identified as factors associated with early marriages. The government and policymakers in Ghana should increase access to and completion of secondary education for girls, as it is crucial in reducing early marriage. Providing programmes that economically empower women and girls can decrease their vulnerability to early marriage. More vigorous enforcement of laws against early marriage is necessary. Engaging with communities, including tribal leaders, is essential to shift cultural attitudes toward early marriage.